Proibição da maconha no Brasil e suas raízes históricas escravocratas - Barros, André; Peres, Marta (Periferia, 2012)
DOI: 10.12957/periferia.2011.3953 Proibição da maconha no Brasil e suas raízes históricas escravocratas